Extensão universitária em ortopedia veterinária - Borsaro, Camila Potério [UNESP]; Minto, Bruno Watanabe [UNESP]; Kawamoto, Fernando Yoiti Kitamura [UNESP]; Dias, Luis Gustavo Gosuen Gonçalves [UNESP]; Macedo, Aline Schafrum [UNESP]; Coelho, Lívia de Paula [UNESP]; Franco, Guilherme Galhardo [UNESP]; Faria, Luis Guilherme de [UNESP]; Gomide, Paula Regina Silva [UNESP]; Sprada, Arícia Gomes [UNESP]; Souza, João Augusto Leonel de [UNESP]; Filgueira, Fabrícia Geovânia Fernandes [UNESP]; et al. (Universidade Estadual Paulista (Unesp), 2015)
The aim of this project is to collaborate in the development and theoretical-practical training of students and professionals, besides that to promote integration and implementation of acts with the population, through internships, promoting contact between professionals, students and owners. In this aspect, production of didactic materials, programs to prevent diseases and data gathering for presentations and publications were performed. In this study, orthopedic conditions of companion animals were characterized in order to inform general public, collect information for learning and for preventive veterinary medicine. With this purpose, a retrospective study of musculoskeletal system affections at the Veterinary Hospital "Governador Laudo Natel", Faculty of Agricultural and Veterinary Sciences, campus Jaboticabal, from May 2014 to June 2015 was conducted. During this period, 585 patient were selected. From those, 557 were dogs (95,21%) and 28 (4,79%) were cats. It was observed in both cases a higher prevalence of 0-4-year-old (45,4% and 92,8%, respectively) patients. It was found that the most prevalent orthopedic cases included fractures (33,69% in dogs and 92,86% in cats) and cranial cruciate ligament rupture (16,84% in dogs). Thus, the achievement of the extension project enabled the integration of several people, allowing further information and knowledge about veterinary orthopedics.

O objetivo deste projeto é colaborar no desenvolvimento e capacitação teórico-prático de alunos e profissionais, além de promover uma integração e implementação de medidas junto à população, por meio de estágios, favorecendo, assim, o contato entre profissionais, alunos e proprietários. Neste aspecto, ocorreu a realização de programas de prevenção das doenças e coleta de dados para apresentação de trabalhos e publicações. Na presente apresentação buscou-se caracterizar as afecções ortopédicas em animais de companhia, visando obter informações que sirvam de instrumento para o aprendizado e medicina veterinária preventiva. Para isto, realizouse o estudo retrospectivo dos casos envolvendo alterações no sistema osteomuscular atendidos no Hospital Veterinário “Governador Laudo Natel”, da Faculdade de Ciências Agrárias e Veterinárias, Campus de Jaboticabal, ocorridos no período de maio de 2014 a junho de 2015. Neste intervalo foram selecionados 585 animais, sendo 557 cães (95,21%) e 28 gatos (4,79%), em ambos observouse uma prevalência maior de animais entre 0-4 anos (45,4% e 92,8%, respectivamente). Constatou-se que os casos ortopédicos de maior prevalência incluíam as fraturas (33,69% em caninos e 92,86% em felinos) e a ruptura do ligamento cruzado cranial do joelho (16,84% em caninos). Desta forma, a realização do Projeto de Extensão possibilitou a integração de diversas pessoas, permitindo a propagação de informações e conhecimento a respeito da ortopedia veterinária.
Keywords: Veterinary orthopedic; Epidemiology; Small animal; Ortopedia veterinária; Epidemiologia; Pequenos animais